Experimental Evaluation of Dry Powder Inhalers during Inhalation and Exhalation Using a Model of the Human Respiratory System (xPULM™) - Richard Pasteka; Lara Alina Schöllbauer; Joao Pedro Santos da Costa; Radim Kolar; Mathias Forjan (MDPI AG, 2022)
Dry powder inhalers are used by a large number of patients worldwide to treat respiratory diseases. The objective of this work is to experimentally investigate changes in aerosol particle diameter and particle number concentration of pharmaceutical aerosols generated by four dry powder inhalers under realistic inhalation and exhalation conditions. To simulate patients undergoing inhalation therapy, the active respiratory system model (xPULM™) was used. A mechanical upper airway model was developed, manufactured, and introduced as a part of the xPULM™ to represent the human upper respiratory tract with high fidelity. Integration of optical aerosol spectrometry technique into the setup allowed for evaluation of pharmaceutical aerosols. The results show that there is a significant difference (p < 0.05) in mean particle diameter between inhaled and exhaled particles with the majority of the particles depositing in the lung, while particles with the size of (>0.5 μm) are least influenced by deposition mechanisms. The fraction of exhaled particles ranges from 2.13% (HandiHaler®) over 2.94% (BreezHaler®), and 6.22% (Turbohaler®) to 10.24% (Ellipta®). These values are comparable to previously published studies. Furthermore, the mechanical upper airway model increases the resistance of the overall system and acts as a filter for larger particles (>3 μm). In conclusion, the xPULM™ active respiratory system model is a viable option for studying interactions of pharmaceutical aerosols and the respiratory tract regarding applicable deposition mechanisms. The model strives to support the reduction of animal experimentation in aerosol research and provides an alternative to experiments with human subjects.